Fractures overseen: Soviet medical experts splitting from the international epistemic community during the interwar period - Schacht, Anastassiya (European review of history, 2024)
Soviet medical science went through a deep and systematic transformation. Initiated in the very early days of the Communist regime, a moment of disrupting and isolating impact uprooted it from its former organizational and epistemic foundations and re-adjusted the expert output and modus operandi to state needs. Professional identities, paradigmatic approaches and everyday practices resulting from these were transformed and forcibly aligned with the expectations of the new powerholders, aligned with the newly formulated party-bound loyalties and secured by the broad array of severe sanctions. This article systematically approaches the dark side of the Soviet interwar transformation in medicine with a special focus on a sample of psychiatric experts. The paper analyses the entanglement between domestic pressures exercised upon scholars by the emerging totalitarianism, forcing them to detach and considerably re-adjust their international ties, while nonetheless trying to remain a part of this cross-border epistemic community. While international contacts did not cease entirely, their expanse, intensity and the very mode of cooperation had to change dramatically so as to fit the new regime´s vision upon medicine. International networks were re-appropriated for the sake of promoting the success of the Communist state, with scholars functioning as involuntary ambassadors of the regime. Though perfectly compatible with the practices and outputs of their fellow experts elsewhere across the globe while exposed to the permanent pressure of political terror at home, Soviet public health and its experts became deeply transformed and detached in manifold ways from their peers and their medical science. Largely overlooked, the early fractures of the interwar period carry on into the Cold War-influenced second half of the twentieth century.
Gesehen am 21.10.2024